Pengaruh Literasi Digital, IPM, UMP terhadap TPT di 5 Provinsi di Indonesia - Zidny Maulida Nafahatir; Dhia Zalfa Nadhifah; Sazkia Jasuma Putri; Anzar Alfat Firdaus (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
Reducing the Open Unemployment Rate (OUR) remains a major challenge in several Indonesian provinces with different development characteristics, including DKI Jakarta, West Java, Banten, the Riau Islands, and Papua. Differences in economic development, labor market structure, and human resource quality contribute to variations in unemployment rates across regions. This study aims to analyze the effect of Digital Literacy, the Human Development Index (HDI), and the Provincial Minimum Wage (PMW) on the Open Unemployment Rate in these five provinces. Digital literacy reflects workforce readiness in responding to technological transformation, HDI represents the quality of education, health, and purchasing power, while PMW indicates wage policy affecting labor costs and employment decisions. This research employs a quantitative approach using panel data from 2015 to 2024 and is analyzed using the Fixed Effect Model (FEM). The results show that individually, digital literacy, HDI, and PMW do not have a significant effect on unemployment. However, simultaneously, these variables significantly influence variations in unemployment across provinces. These findings highlight the importance of integrated labor market policies that consider regional characteristics to achieve sustainable unemployment reduction.